The Use of Birth Ball as A Non-Pharmacological Complementary Therapy in The Reduction of Labor Pain in Phase 1 - Desyanti, Harwin Holilah; Sasriawati, Sasriawati (Jurnal Indonesia Sosial Sains, 2024)
Childbirth is the process of expelling the fetus to the placenta, the process of giving birth is identical to pain, while to reduce this pain, non-pharmacological methods are carried out, one of which is the Birth Ball method. This study aims to evaluate the effectiveness of using birth ball as a non-pharmacological complementary therapy in reducing labor pain in the first stage. The method used was a narrative literature review by searching for relevant articles on Google Scholar using keywords such as “Birth ball” and “Labor pain”. Inclusion criteria included Indonesian-language articles published between 2021-2023. Of the six studies analyzed, it was found that birth ball use significantly reduced the intensity of labor pain. These studies showed that birth balls can accelerate cervical opening and reduce anxiety of laboring mothers through movements that increase endorphin release. In conclusion, birth balls are effective as an alternative method to reduce labor pain in Stage I, providing the added benefit of increasing maternal comfort and relaxation during the labor process. This study suggests the use of birth ball as part of midwifery practice to reduce labor pain non-pharmacologically.